2017
DOI: 10.1177/1759720x17719850
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate, blood pressure and markers of arterial function in patients with rheumatoid arthritis: a repeated cross-sectional study

Abstract: Background: Methotrexate (MTX) treatment in rheumatoid arthritis (RA) has been associated with lower cardiovascular risk compared to other disease-modifying antirheumatic drugs (DMARDs). We sought to identify whether the MTX-associated cardioprotection involves changes in blood pressure (BP) and/or arterial function. Methods: Clinic and 24-hour peripheral and central systolic and diastolic BP (SBP and DBP), augmentation index (AIx), pulse wave velocity (PWV) and plasma asymmetric dimethylarginine (ADMA) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 80 publications
2
36
2
1
Order By: Relevance
“…In a study in patients with rheumatoid arthritis, methotrexate treatment did not reduce arterial stiffness [102]. By contrast, in a repeated cross-sectional study of patients with rheumatoid arthritis, methotrexate treatment was independently associated with reduced pulse-wave velocity, a marker of arterial stiffness, measured over 24 hours, after adjusting for age, gender, body mass index, rheumatoid arthritis disease severity and use of folic acid [103].…”
Section: Methotrexate Endothelial Function Arterial Stiffness and mentioning
confidence: 85%
See 1 more Smart Citation
“…In a study in patients with rheumatoid arthritis, methotrexate treatment did not reduce arterial stiffness [102]. By contrast, in a repeated cross-sectional study of patients with rheumatoid arthritis, methotrexate treatment was independently associated with reduced pulse-wave velocity, a marker of arterial stiffness, measured over 24 hours, after adjusting for age, gender, body mass index, rheumatoid arthritis disease severity and use of folic acid [103].…”
Section: Methotrexate Endothelial Function Arterial Stiffness and mentioning
confidence: 85%
“…Observational cross-sectional and prospective studies in rheumatoid arthritis have also shown that methotrexate use is associated with lower systolic and diastolic blood pressure and reduced incidence of hypertension, when compared to other DMARDs or no treatment [103][104][105][106][107][108]. In one of these studies, the associations between methotrexate treatment and lower blood pressure were also observed for 24-hr measures of peripheral and central blood pressure [103]. Twenty-four-hour averages of systolic and diastolic blood pressure are significantly superior to clinical blood pressure in terms of cardiovascular risk stratification [109].…”
Section: Methotrexate Endothelial Function Arterial Stiffness and mentioning
confidence: 99%
“…При использовании метотрексата шанс достижения целевых значений АД был выше на 9%. Также продемонстрирована ассоциация между приемом метотрексата и более низкими значениями скорости пульсовой волны, центрального, систолического и диастолического АД при офисном измерении и суточном мониторировании у больных РА [21].…”
Section: синтетические базисные противовоспалительные препараты метотunclassified
“…Furthermore, methotrexate, the drug of choice as first-line treatment, is associated with a consistent reduction in mortality (70%), a decline in the rate of total cardiovascular events (around 28%), and up to 18% lower risk of myocardial infarction in patients with RA [31]. Unlike the anti-TNF agents, methotrexate is not related to a significant decrease in strokes and major adverse cardiac events; nevertheless, it seems that the risk of heart failure is also decreased [1,2,31,32].…”
Section: Cardiovascular Safety Of Non-biologic and Biologic Anti-rheumentioning
confidence: 99%